2021
DOI: 10.4103/ijo.ijo_1192_21
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous fungal endopthalmitis treated with intravitreal caspofungin in a COVID-19 recovered patient: A case report

Abstract: We present a case of endogenous fungal endophthalmitis in a nondiabetic, nonhypertensive patient who recovered from COVID-19 infection. Endogenous fungal endophthalmitis in an immunocompetent individual is quite uncommon. The organism in our patient was resistant to amphotericin and voriconazole and was successfully treated with intravitreal caspofungin. The rarity of an opportunistic nosocomial infection in an immunocompetent person with a drug-resistant organism prompted us to write this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Amphotericin B and voriconazole are commonly used antifungal agents and have exhibited favorable effects in controlling inflammation ( Yang et al., 2011 ; Bae and Lee, 2015 ; Zhao et al., 2015 ; Bienvenu et al., 2020 ). What’s more, several case reports published in recent years have shown that in the cases of resistant fungal endophthalmitis, intravitreal caspofungin, the first approved antifungal echinocandin, can be an ideal and safe alternative to the former two ( Danielescu et al., 2017 ; Yadav et al., 2017 ; Von Jagow et al., 2020 ; Nakhwa, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Amphotericin B and voriconazole are commonly used antifungal agents and have exhibited favorable effects in controlling inflammation ( Yang et al., 2011 ; Bae and Lee, 2015 ; Zhao et al., 2015 ; Bienvenu et al., 2020 ). What’s more, several case reports published in recent years have shown that in the cases of resistant fungal endophthalmitis, intravitreal caspofungin, the first approved antifungal echinocandin, can be an ideal and safe alternative to the former two ( Danielescu et al., 2017 ; Yadav et al., 2017 ; Von Jagow et al., 2020 ; Nakhwa, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…13 In the present case, the right eye was classified as stage III while the left eye was categorized as stage I. Consequently, a PPV was performed on the right eye, followed by systemic antifungal therapy featuring oral fluconazole administration. For patients with EFE who have not yet developed retinal detachment, that is, patients with EFE before stage IV, it has been reported that intravitreal injection is also an alternative treatment modality, including caspofungin, 14 amphotericin B, 15 and voriconazole. 16 Endogenous fungal endophthalmitis poses a significant threat to ocular health and represents a rare yet serious complication of fungemia.…”
Section: Discussionmentioning
confidence: 99%
“…An intravitreal dose of 50 µg/0.1 ml is safe,[ 18 ] and there are reported successes in multi-antifungal agent-resistant fungal endophthalmitis. [ 19 ] Posaconazole is a triazole compound that disrupts the acyl chains of phospholipids, impairs the functions of certain membrane-bound enzyme systems such as ATPase, and inhibits fungal growth. It is reportedly more potent than the other two azole compounds, voriconazole and itraconazole.…”
Section: Discussionmentioning
confidence: 99%